Efektifitas Prenatal Yoga Terhadap Nyeri Melahirkan: Studi Tinjauan Literatur Sistematik: The Effectiveness of Prenatal Yoga on Labor Pain: A Systematic Literature Review - Zesika Intan Navelia; Dian Monalisa Rusliani (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Background: Prenatal Yoga is a type of body, mind, and mental exercise that can reduce risk of preterm delivery, caesarean section, and fetal death. The objective of the present study was to determine the effect of Yoga on labor pain. Methods: This was a systematic literature review using seven electronic databases for searching: ScienceDirect, PubMed, GoogleScholar, Cochrane, ResearchGate, and Portal Garuda. Randomized Controlled Trial and Quasy Experiment studies examining yoga met the inclusion criteria. Results: Of 578 non-duplicated studies. 7 met criteria for full-text reviews. The finding in studies suggest prenatal yoga may be safe and may effectively decrease pain level while labor. Conclussion: Yoga appear to be safe and may reduce pain on labor. However, due to the limited number of high-quality Randomized Controlled Trials study, more reseach are needed to draw conclusions about improvement in other pregnancy outcomes.